2018
DOI: 10.1016/j.theriogenology.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spermatozoal lipidomic profile on the cryoresistance of frozen spermatozoa from stallions

Abstract: The membrane of spermatozoa, which contributes to cellular cryoresistance, contains numerous lipids with a composition that directly affects membrane fluidity and the fertilization process. In light of variations in the degree of sensitivity in equine seminal freezing, this study aimed to correlate equine semen lipids with post-thawing characteristics of spermatozoa. We used ejaculates from 34 stallions, which were evaluated (total motility ≥ 60%), frozen and thawed and reevaluated for motility of spermatozoa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…As the seminal plasma components differ between good and poor freezers [18], we can assume that collected ejaculate from poor freezers has predetermined freezability. This is further supported by a study by Cabrera et al [32], who found different lipidomic profiles in poor compared to good freezers and linked this change to freezability.…”
Section: Discussionsupporting
confidence: 73%
“…As the seminal plasma components differ between good and poor freezers [18], we can assume that collected ejaculate from poor freezers has predetermined freezability. This is further supported by a study by Cabrera et al [32], who found different lipidomic profiles in poor compared to good freezers and linked this change to freezability.…”
Section: Discussionsupporting
confidence: 73%
“…The lipid profile of equine SP has been studied, 50‐52 and the lipidomic profile of stallion ejaculated spermatozoa was seen to be related to the cryotolerance capacity, 53 as previously described for human spermatozoa 54 . In our results, it seems that having more PUFA is better to favor freezing (Figure 4B) although a, greater proportion of SFA did not.…”
Section: Discussionmentioning
confidence: 76%
“…According to previous research, a positive correlation between phosphatidylcholines abundance and the sperm motility in thawed sperm had been found ( 12 , 51 ). As the biomarkers related to sperm freezability, PC may affect the motility, membrane integrity and lipid peroxidation ( 13 , 52 ). As the primary component of the plasma membrane, phosphatidylcholines are crucial for controlling the function of the membrane, particularly membrane fusion, fluidity and protein binding ( 53 ).…”
Section: Discussionmentioning
confidence: 99%